1999
DOI: 10.1038/15110
|View full text |Cite
|
Sign up to set email alerts
|

Increased baculovirus susceptibility of armyworm larvae feeding on transgenic rice plants expressing an entomopoxvirus gene

Abstract: We have introduced an entomopoxvirus gene encoding a virus enhancing factor (EF) into rice, which resulted in high-level accumulation of the EF in the transgenic plants. The introduced gene was stably inherited in the progeny of the primary transformants, as shown by analysis of their genomic DNA. Bioassays for insect susceptibility to baculovirus infection showed that armyworm larvae feeding on the transgenic rice had increased susceptibility to a Nucleopolyhedrovirus. Thus, introduction of the EF gene into p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0
1

Year Published

2001
2001
2015
2015

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(7 citation statements)
references
References 24 publications
0
6
0
1
Order By: Relevance
“…A CBM33 single domain protein is strongly up-regulated as part of the stress response of Enterococcus faecalis [69]. There is also convincing evidence showing CBM33s to be essential for the infectivity of insect-larvae targeting viruses [70,71], which could be a consequence of CBM33 effects on insect chitin. It is conceivable that in some cases the CBM33s have a mere binding function.…”
Section: Enzymatic Degradation Of Cellulosementioning
confidence: 99%
“…A CBM33 single domain protein is strongly up-regulated as part of the stress response of Enterococcus faecalis [69]. There is also convincing evidence showing CBM33s to be essential for the infectivity of insect-larvae targeting viruses [70,71], which could be a consequence of CBM33 effects on insect chitin. It is conceivable that in some cases the CBM33s have a mere binding function.…”
Section: Enzymatic Degradation Of Cellulosementioning
confidence: 99%
“…Remarkably, in larval cofeeding experiments, spindles also enhance the insecticidal activity of unrelated oral pathogens such as baculovirus (8) and the Bacillus thuringiensis (Bt) toxin (9) by up to three orders of magnitude. This effect on virulence prompted their use as synergistic additives to common bioinsecticides, for instance by transgenic expression of spindles in plants to improve the effectiveness of baculovirus insecticides (10).…”
mentioning
confidence: 99%
“…In microbial control of insect pests, the combination of two viruses that interact by synergism may purposely be used to enhance the effect of a viral insecticide formulation. Hukuhara et al (1999) have suggested the use of a virus enhancing factor from PSEV as an additive of NPV insecticides. For the opposite purpose, that is to say, to protect useful insects from viral infections, the knowledge of multiple virus interactions should also be useful.…”
Section: Resultsmentioning
confidence: 99%